Giving undergraduate nursing students international experiences: Issues and strategies - Sue Turale (2020)
© 2020 John Wiley & Sons Australia, Ltd Educational institutions began international student placements or exchanges in earnest in the 1990s, with varying degrees of success. Although nursing education in a number of countries has embraced giving undergraduate students the opportunity of international experiences, this is still not the norm in many countries, nor within all nursing schools within a country. In our rapidly globalizing world, it is critical that students are given opportunities internationally to be better prepared for practice, to achieve a global mindset, and to take their place as future global citizens through international experiences. Evidence from the literature shows positive effects on nurses having had international experiences to broaden their horizons, examine other cultures, grow their cultural competence, share and gain knowledge with others, and build their capacity for future practice in an increasingly globalized world. Our focus here is on providing students with short-term undergraduate exchanges or placements in international settings, and encouragement for nursing institutions to develop international partnerships that are sustainable. Some implications for nurse educators and other staff involved in international exchanges are also considered.